Effect of Organic Material Type and Proportion on the Physical and Mechanical Properties of Vegetation-Concrete - Daxiang Liu; Baohua Zhang; Yueshu Yang; Wennian Xu; Yu Ding; Zhenyao Xia (Advances in Materials Science and Engineering)
Vegetation-concrete is one of the most widely used substrates in ecological slope protection engineering. The porosity of the vegetation-concrete must be high enough to satisfy the growth needs of the plant roots, while the mechanical properties must be strong enough to satisfy the self-stability requirement of the substrates on the slope. It is necessary to balance these two aspects in the design of vegetation-concrete. As one of the main components in vegetation-concrete, organic material has a remarkable effect on both the porosity and the mechanical properties of the substrate. In this paper, four types of common organic materials (rice husks, sawdust, and corn distillers’ and unhulled rice distillers’ grain) are chosen to research the effect of the organic material type and proportion on the porosity and mechanical properties of the substrate. The experimental results show that the porosity of samples containing corn distillers’ grain is clearly higher than those of the other samples types, while situation of the mechanical properties is the opposite. It can be concluded that organic material with a large grain size is not suitable for use in vegetation-concrete directly and needs to be crushed before use to prevent crack formation. The research results also show that the rates of increase in porosity decrease with more organic material added, while the rates of decrease in the unconfined compressive strength and the elasticity modulus increase. From a comprehensive consideration of the required mechanical properties and plant growth, organic material with a small grain size is most suitable for use in vegetation-concrete, and the suitable proportion is between 7% and 9%.